Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitors versus single agent chemotherapy as second‐line treatment for non–small‐cell lung cancer wild‐type or unknown status for EGFR - Créquit, Perrine (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The aim of this systematic review is to evaluate the effectiveness and safety of EGFR‐TKIs versus single‐agent chemotherapy as second‐line treatments in patients with advanced NSCLC and wild‐type or unknown status for EGFR.